KESANTUNAN TINDAK TUTUR DALAM BERBAHASA ACEH ANTARA MASYARAKAT GAMPONG COT PANYANG DENGAN MASYARAKAT GAMPONG PASI RAWA DI KECAMATAN KOTA SIGLI - Nofiana S Nofiana S; Hayatun Rahmi (Jurnal Sains Riset, 2022)
This research is entitled "Politeness of Speech Acts in Acehnese Language Between the Community of Gampong Cot Panyang and the Community of Gampong Pasi Rawa in Kota Sigli District". The formulation of the problem in this research is how is the level of politeness and form of politeness in Acehnese language between the people of Gampong Cot Panyang and the people of Gampong Pasi Rawa in Kota Sigli District? This study aims to determine the level of politeness and the form of the politeness of the Acehnese language between the people of Gampong Cot Panyang and the people of Gampong Pasi Rawa in Kota Sigli District. This study uses a qualitative approach. The type of research used is descriptive research. The data collection technique was carried out using documentation techniques, while the data analysis techniques were carried out using qualitative descriptive techniques and pragmatic analysis. The results of the study indicate that the speech acts of speech in Acehnese language between the Gampong Cot Panyang community and the Gampong Pasi Rawa community contained in the locutionary speech act are the meanings of informing, asking, and ordering.Keywords : politeness, speech acts, Acehnese language